Commutation and Intensification of Judicial Punishment after Award Issuance in Procedure Code of Iran - Najafi, Mehdi; Soltanfar, Gholamreza (Journal of History Culture and Art Research, 2017)
Punishment commutation is one of issues considered by legislature in different periods. In Islamic Penal Code approved in 2013, this issue is also addressed by legislature and some conditions and regulations are considered for it. In total, the attitude of Articles 37 and 38 of Islamic Penal Code approved in 2013 is more clear, transparent and organized than Penal Code approved in 1991. Seemingly, Islamic penal Code 2013 has chosen a better approach than Islamic Penal Code 1991 to address punishment commutation issue and it is closer to Law of European countries. Islamic Penal Code approved in 2013 expresses cases related to punishment commutation or exemption from it in detail through Articles 37, 38, and 39; also, Ta’zir punishments are divided into eight degrees in Article 9, which is a creative manner. It is legislated by New Criminal Procedure Code and other new rules through new Articles, the final award can be deviated or defendant can be exempted even after award issuance and its sentencing at the award enforcement step. In this case, some conditions are considered as follows: good manner or lack of good manner, commitment of crimes that had been enforceable before but have not been prosecuted still (multiplicity of offenses) or crimes that their final award is issued without any influence on punishment of sentenced person. Commutation or intensification of judicial punishment, which the subject of this research, is distinguished from commutation or intensification of legal punishment and only reduction or increase in punishment, with any level, can be case of commutation or intensification because the criterion for punishment commutation or intensification is the punishment contained in awards not the legal punishment addressed by legislature.